SEMIOTIKA RIFFATERRE DALAM PUISI “LAGU SEORANG GERILYA” KARYA W.S. RENDRA - Zahrani, Fairuz Annisa; Susilo, Rini Febrianti; Ratih, Rina (Jurnal Bahasa Indonesia Prima (BIP), 2023)
The poem entitled "Song of a Guerrilla" is a great literary work that is able to express the contents of his thoughts into beautiful poetic verses that make the author interested in researching poetry from W.S Rendra. The purpose of this study is to describe a guerrilla song poem using the study of riffatere semiotics. This research uses a qualitative descriptive approach by describing the facts that are then analyzed. Research data in the form of words, phrases, clauses, sentences contained in poetry texts. Riffatere semiotic reading steps: (1) Heuristic reading and hermeneutic reading, (2) Indirectness of expression, (3) Determining matrices, models, and variants, (4) Hypogram of W.S. Rendra's song of a guerrilla poem, and (5) Summing up data and writing reports. The results of this study describe the meaning that poets want to convey through poetry is about their lovers until the end of their lives on the battlefield. The matrix of a guerrilla's song poem is struggle, resilience, oppression. The model on a guerrilla's song poem uses symbolic and metaphorical meanings.